Single-mode coherent synchrotron radiation instability of a bunched beam - S. Heifets (Physical Review Special Topics. Accelerators and Beams, 2003)
The coherent synchrotron radiation instability may be driven at the shielding threshold by a single mode excited in the beam pipe. Such a problem may have general interest for other one-mode dominated problems arising in plasma, free-electron laser theory, and microwave instability. The problem may have practical interest if the steady state exists but requires the study of the nonlinear regime of instability. The results of the study, both analytic and numerical, are presented in the coasting beam approximation and for a bunched beam.